ACVR2A promoter polymorphism rs1424954 in the Activin-A signaling pathway in trophoblasts. Issue 4 (April 2015) - Thulluru, H.K.; Michel, O.J.; Oudejans, C.B.M.; van Dijk, M.
Abstract Introduction Pre-eclampsia is a pregnancy-specific disorder and characterized by reduced trophoblast invasion and reduced spiral artery remodeling in the first trimester placenta. A polymorphism located in the promoter region of ACVR2A (rs1424954 (A > G)) has previously been shown to be significantly associated with pre-eclampsia. Methods The effects of this variant on ACVR2A expression and its function in the Activin-A signaling pathway were studied by transfections in SGHPL-5 extravillous trophoblasts followed by qRT-PCR. Results Here we show that the ACVR2A promoter susceptibility variant causes a downregulation of ACVR2A expression. We also provide evidence for transcription of a so-called PROMPT (PROMoter-uPstream-Transcript) in the opposite direction of ACVR2A, containing the polymorphism, and downregulated when the susceptibility allele is carried, which either shares the same promoter as ACVR2A or is a non-coding RNA that is able to enhance ACVR2A transcription. Furthermore, when the effect of the susceptibility variant is mimicked by knockdown of ACVR2A, physiologic concentrations of Activin-A cause a reduction in NODAL mRNA expression in the SGHPL-5 trophoblasts, indicative of a protective effect as reduction in NODAL expression is associated with an increase in trophoblast invasion. However, at pathologic levels of Activin-A, as found in pre-eclampsia, this effect is no longer seen, and we show this is potentially caused by a lack of downregulation of ACVR2B. Discussion The combined data suggest a double hit phenomenon in which the first hit, the promoter variant, together with the second hit, pathological levels of Activin-A, lead to high levels of NODAL, associated with reduced trophoblast invasion and observed in pre-eclamptic placentas.